ADULT-ONSET CYSTIC HYGROMA IN AXILLA: A RARE CASE REPORT FROM INDIA AND LITERATURE REVIEW: (case report) - Pandey, R.; Kumar, R.; Maheshwari, S.; Singh, T. S.; Bhalla, S.; Khan, I. D. (International Journal of Medicine and Medical Research, 2021)
Background. Cystic hygroma (CH), occurs in 1/6000 live births and in 90% of cases develops in age less than 2 years old. They are mainly located in cervicofacial region. Adult-onset CH is very rare. Objective. The aim of this study is to review literature to discuss the clinical presentation, diagnosis, and treatment of CH in adults through a case report of unilocular CH in the axillary region in an adult male from India. Methods. A first case report of unilocular CH in axillary region in an adult male from India is being investigated. Results. Here we report a case of unilocular CH in the axillary region in a 49-year-old male with a 14x16x8 cm cystic swelling in left axilla with a history of aspiration failure. Contrast-enhanced MRI (CEMRI) showed well-defined thin walled, unilocular cystic lesion which appeared hyperintense on T2 & STIR and hypointense on T1W1 and showed thin peripheral rim of enhancement on post contrast images. The patient underwent surgical excision and the diagnosis of a pathological CH was established. His postoperative recovery was uneventful and had no evidence of recurrence. Conclusion. Due to rarity of adult-onset unilocular CH in axilla, its evaluation for prompt diagnosis and definitive treatment to prevent recurrence and complications is urgent. Furthermore, this is the first reported case from India which has been successfully managed at a peripheral hospital in Northeast-India and our report of this case contributes to the evidences supporting the role of CH in a differential diagnosis for masses in the adult axilla, especially in acute phase with no predisposing factors.